In Vivo Validation of Alternative FDXR Transcripts in Human Blood in Response to Ionizing Radiation - Cruz-Garcia, Lourdes; O'Brien, Grainne; Sipos, Botond; Mayes, Simon; Tichý, Aleš; Sirák, Igor; Davídková, Marie; Marková, Markéta; Turner, Daniel J; Badie, Christophe (International journal of molecular sciences, 2020)
Following cell stress such as ionising radiation (IR) exposure, multiple cellular pathways are activated. We recently demonstrated that ferredoxin reductase (FDXR) has a remarkable IR-induced transcriptional responsiveness in blood. Here, we provided a first comprehensive FDXR variant profile following DNA damage. First, specific quantitative real-time polymerase chain reaction (qPCR) primers were designed to establish dose-responses for eight curated FDXR variants, all up-regulated after IR in a dose-dependent manner. The potential role of gender on the expression of these variants was tested, and neither the variants response to IR nor the background level of expression was profoundly affected; moreover, in vitro induction of inflammation temporarily counteracted IR response early after exposure. Importantly, transcriptional up-regulation of these variants was further confirmed in vivo in blood of radiotherapy patients. Full-length nanopore sequencing was performed to identify other FDXR variants and revealed the high responsiveness of FDXR-201 and FDXR-208. Moreover, FDXR-218 and FDXR-219 showed no detectable endogenous expression, but a clear detection after IR. Overall, we characterised 14 FDXR transcript variants and identified for the first time their response to DNA damage in vivo. Future studies are required to unravel the function of these splicing variants, but they already represent a new class of radiation exposure biomarkers.
Keywords: alternativní sestřih; upregulace; krev; Humans; vztah dávky záření a odpovědi; Up-Regulation; lidé středního věku; Dose-Response Relationship, Radiation; gene expression; regulace genové exprese; ionizující záření; Radiation, Ionizing; Female; qPCR; dospělí; alternative transcript; lidé; biodosimetry; Alternative Splicing; oxidoreduktasy; Adult; ženské pohlaví; Gene Expression Regulation; Male; Middle Aged; nanopore sequencing; splice variants; FDXR; Neoplasms; Blood; nádory; poškození DNA; DNA Damage; mužské pohlaví; Oxidoreductases; ionizing radiation